1979
DOI: 10.1677/joe.0.0820409
|View full text |Cite
|
Sign up to set email alerts
|

Secretion Rate and Metabolic Clearance Rate of Prolactin in the Rat During Mid- And Late Lactation

Abstract: The prolactin concentration in the plasma of lactating rats rose less rapidly and attained a significantly lower plateau level in response to suckling on day 20--21 of lactation than it did on day 13--14 of lactation. Neither differences in suckling stimulation of the older pups nor a higher metabolic clearance rate (MCR) of prolactin were implicated in the reduced prolactin concentration seen in the late-lactating rats. The MCR was, in fact, slightly reduced in both conscious and late-lactating rats anaesthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…However, the present results indicate that the metabolic half-life of prolactin in the plasma is similar in early, mid-and late lactation. This is in accordance with a study by Grosvenor and Whitworth [1979] who found a simi lar half-life for prolactin in mid-and late lac tation. From the foregoing it does not seem likely that the decreased response of plasma prolactin to suckling in advancing lactation is caused either by a reduced suckling stimulus of pups, or by an increased clearance of pro lactin from the circulation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the present results indicate that the metabolic half-life of prolactin in the plasma is similar in early, mid-and late lactation. This is in accordance with a study by Grosvenor and Whitworth [1979] who found a simi lar half-life for prolactin in mid-and late lac tation. From the foregoing it does not seem likely that the decreased response of plasma prolactin to suckling in advancing lactation is caused either by a reduced suckling stimulus of pups, or by an increased clearance of pro lactin from the circulation.…”
Section: Discussionsupporting
confidence: 93%
“…This suggestion is not supported by the results of experiments in which at later stages of lacta tion the litters were replaced by younger fos ter pups [Mattheij et al. 1979;Selmanoff and Wise, 1981;Grosvenor and Whitworth, 1979]. An alternative interpretation is that the capacity of the pituitary to synthesize and/or secrete prolactin depends on the lacta tional age of the dam.…”
Section: Introductionmentioning
confidence: 99%
“…The appropriate dose will probably also be affected by a number of other factors, including the route of administration (oral versus systemic or subcutaneous injection), the number of offspring being nursed (intensity of suckling and other exteroceptive stimulation), and the stage in lactation when it is applied [since prolactin secretion in response to suckling may be reduced in the later stages of lactation (Grosvenor & Whitworth, 1979)l. Furthermore, the experimenter must consider whether complete or partial suppression of lactation is most appropriate.…”
Section: Dose and Administrationmentioning
confidence: 99%
“…To study the effect of lactation, we focused on the timing of changes in prolactin and oxytocin, as they both are the major hormones during this period. Prolactin is known to be at its highest level on PP13 and to decrease thereafter in lactating rats [ 15 ]. On the other hand, intracerebral oxytocin is constantly maintained at a high level as long as rats receive nipple suckling stimulation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%